Blood Pressure and Haematological Indices in Twelve Communities in Ashanti, Ghana. (5th April 2018) - Plange-Rhule, Jacob; Kerry, Sally M.; Eastwood, John B.; Micah, Frank B.; Antwi, Sampson; Cappuccio, Francesco P.
Abstract : Hypertension is the most important risk factor for cardiovascular mortality and morbidity in Sub-Saharan Africa. In western populations, high haemoglobin levels are associated with raised BP unlike in Sub-Saharan Africa where there is a paucity of data. Our study examines the association between haematological indices with BP variables. Weight, height, BP, and whole blood indices of viscosity (Hb, haematocrit, RBC count, and MCV) were measured in 921 adults (340 men, 581 women; aged 40–75) in 12 communities in Ghana. Mean values for Hb (12.3 g/dl ± 1.7 SD), haematocrit (36.7 % ± 5.2 ), RBC (4.10 million/ μ L ± 0.64), and MCV were lower than reference values used in Sub-Saharan Africa. Mean BMI was 21.1 ± 4.1 indicating a lean population. Systolic BP increased by 1.0 mmHg (95% CI 0.5–1.5), p < 0.001, for women and 0.5 (0.1–1.0), p = 0.027, for men per unit increase in haematocrit. Similar relationships were found for Hb and RBC but not for MCV or platelets. The relationships were weaker when adjusted for BMI, 0.7 mmHg (0.2–1.2) in women and 0.5 (0.0–1.0) in men. Findings for diastolic BP were similar. Overall haematological indices were low. We have found a significant, positive relationship between BP, Hb, Haematocrit, and RBC count in our population.